2019
DOI: 10.1111/bcp.13945
|View full text |Cite
|
Sign up to set email alerts
|

Trends in utilization and dosing of antipsychotic drugs in Scandinavia: Comparison of 2006 and 2016

Abstract: Aims: The aim of this study was to investigate time trends in dosing and prevalence of antipsychotic prescriptions in Scandinavia.Methods: We retrieved data on antipsychotic use between 2006 and 2016 from Danish, Norwegian and Swedish national prescription registers. For each antipsychotic, we calculated prevalence of use and mean doses, overall and for specific age groups (young, adults and elderly). Results: Antipsychotic use in Scandinavia increased from 16.5 to 17.2 users/1000 inhabitants between 2006 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 38 publications
(63 reference statements)
3
40
0
1
Order By: Relevance
“…The exclusion of a substantial type 2 diabetes risk with low-dose quetiapine is important, given the increasing number of low-dose quetiapine users worldwide. 3 , 34 Many years of critical attention to the long-term use of benzodiazepines and hypnotics is a possible driver of this increase, and could have created a new public health problem, if low-dose quetiapine were associated with considerable type 2 diabetes risk. However, the high NNH (684) suggests that this risk is likely not important for the individual user or from a public health perspective, as it will not result in a substantial number of new type 2 diabetes cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of a substantial type 2 diabetes risk with low-dose quetiapine is important, given the increasing number of low-dose quetiapine users worldwide. 3 , 34 Many years of critical attention to the long-term use of benzodiazepines and hypnotics is a possible driver of this increase, and could have created a new public health problem, if low-dose quetiapine were associated with considerable type 2 diabetes risk. However, the high NNH (684) suggests that this risk is likely not important for the individual user or from a public health perspective, as it will not result in a substantial number of new type 2 diabetes cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other antipsychotic medications commonly used in low doses, such as olanzapine or risperidone, are also associated with metabolic disturbances, 38 and not used off-label to the same extent as quetiapine. 6 , 34 SSRIs are not an ideal comparator because of their association with weight gain 39 and metabolic disturbances. 32 , 40 However, these associations are likely to be inflated from population-based comparisons and not solely represent the potential obesogenic or diabetogenic effect of SSRIs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, efficacy of quetiapine for improving behavioral and psychological symptoms of dementia is not well established and findings from randomized clinical trials are inconclusive 24,25 . Nevertheless, off‐label use of quetiapine and other antipsychotics for dementia has been reported in multiple Scandinavian countries 26 and one study found that 46% of quetiapine‐treated patients with dementia received quetiapine for sleep disorders 27 …”
Section: Discussionmentioning
confidence: 99%
“…However, a pronounced decrease in the use of benzodiazepine analogues has been observed over the same period ( Danish Health Data Authority ), which might have been replaced, at least partly, by low-dose use of antipsychotics acting as anxiolytics or hypnotics. The quite low average quantities dispensed to each user lends some support to this hypothesis (Højlund et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies addressing the underlying drivers of antipsychotic utilisation are scarce (Olfson et al ., 2012 ; Baandrup and Kruse, 2016 ), and prior studies on overall antipsychotic utilisation commonly lack information on associated diagnoses (Hálfdánarson et al ., 2017 ; Højlund et al ., 2019 ), or were confined to patients with psychiatric diagnoses or contacts (Olfson et al ., 2012 ; Baandrup and Kruse, 2016 ). Thus, these studies did not assess the entire population of users treated in general practice, private psychiatric practice or other medical specialties than psychiatry.…”
Section: Introductionmentioning
confidence: 99%